1984
DOI: 10.1038/clpt.1984.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicotine chewing gum on plasma nicotine levels of cigarette smokers

Abstract: This study was designed to determine whether the use of nicotine chewing gum modifies the inhalation and absorption of nicotine by cigarette smokers. Our subjects, 12 subjects who smoked cigarettes regularly, were studied for 4 days. On the first day, they smoked as usual, and on the second, third, and fourth days they also chewed a placebo gum, 2-mg nicotine gum, or 4-mg nicotine gum. They were instructed to smoke as usual throughout the study. Mean plasma nicotine concentration was 29.5 ng/ml with the placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The evidence for complete or precise nicotine titration, as postulated by some authors (Ebert et al, 1984;Russell, 1989), is certainly rather sparse.…”
Section: Smoking and Simultaneous Nicotine Supplementationmentioning
confidence: 93%
“…The evidence for complete or precise nicotine titration, as postulated by some authors (Ebert et al, 1984;Russell, 1989), is certainly rather sparse.…”
Section: Smoking and Simultaneous Nicotine Supplementationmentioning
confidence: 93%
“…supports the view that the individual smoking pattern is modified to regulate nicotine intake.' Ebert, McNabb, and Snow, 1984. Twelve recoveringalcoholic inpatient smokers were instructed to smoke as they felt the urge for the duration of the 4-day study.…”
Section: Acute Dosing Systemsmentioning
confidence: 99%
“…Heart rate and blood pressure were not significantly affected by nicotine gum. Taken together, the present results confirm that responses to nicotine in the gum preparation are orderly and related to dose, and the results suggest that the efficacy of treating tobacco dependence with nicotine gum may be enhanced by increasing the administered dose.Although studies have shown that the administration of nicotine polacrilex (nicotine gum) decreases subsequent cigarette smoking, as determined by behavioral measures such as number of cigarettes smoked (Brantmark et al 1973;Russell et al 1977;Herning et al 1985; Henningfield 1985, 1986), or physiologic measures such as expired air CO level (Russell et al 1976aEbert et al 1984), none of these studies has demonstrated reliable decreases in desire to smoke (often termed "craving") and none has demonstrated significant decreases in both behav-* Present address: 623 Traylor, The ioral and physiologic measures of cigarette smoking. Additionally, there are problems in interpreting the results of previous studies, since some were not placebo controlled, few have compared multiple dose levels of nicotine gum to placebo, and none have tested nicotine gum using a preparation and procedure previously shown to be sensitive to the effects of other psycho-active drugs on cigarette smoking.…”
mentioning
confidence: 99%
“…Thus, across studies, results are often divergent, leaving open questions such as whether nicotine gum might alter gross elements of smoking behavior (e.g., cigarettes smoked) which are compensated for by more subtle changes (e.g., puffing parameters), resulting in no functional change in tobacco product intake or vice versa. For example, Ebert et al (1984) found a significant decrease in peak expired air CO levels following cigarette smoking when both 2 mg and 4 mg preloading doses were compared to placebo. However, there was no significant change in the number of cigarettes smoked across dose.…”
mentioning
confidence: 99%